'It's nothing you could ever prepare anyone for': the experiences of young people and their families following parental stroke. (21st March 2018) - Coppock, Clare; Ferguson, Scott; Green, Anna; Winter, David
ABSTRACT: Aims : This study sought to explore the experiences of young people (aged 8–16) and their families following parental acquired brain injury (ABI), with the aim of developing an understanding of the ways in which members of a family make sense of events post-injury, and to consider the implications of different perspectives on adjustment and coping. Design : The study applied a qualitative approach using a thematic analysis methodology. Procedure : Individual semi-structured interviews were conducted with 10 individuals from three families affected by parental stroke. Results : Findings suggested that post-injury, families experienced a period of uncertainty in which they were required to renegotiate their roles and adjust to the loss associated with parental stroke. Additionally, the psychosocial wellbeing of young people was negatively affected, whilst protective and coping strategies were recognised. Conclusions : The research offers an insight into the processes that may contribute to patterns of interpersonal relating that could negatively impact on adjustment. Provision of adequate information, psychological and practical support during recovery may therefore be crucial elements of supporting young people and their families in adjusting to the challenges posed by stroke.